Retraction Note: The microRNA-130a-5p/RUNX2/STK32A network modulates tumor invasive and metastatic potential in non-small cell lung cancer - Fang Ma; Yangchun Xie; Yiyu Lei; Zengshuyu Kuang; Xianling Liu (BMC Cancer)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12885-020-07056-0.